Effectiveness of project PFRATH on reading performance of grade one pupils in mother tongue based-multilingual education - Hubag, Dina M (2021)
This study aims to determine the effectiveness of Project “Parents Facilitates Reading at Home” (PFRATH) to the reading performance of Grade One Pupils of Tuban Elementary School, Santa Cruz South District in Mother Tongue-Based Multilingual Education (MTB-MLE). The respondents of this study were the forty-six (46) Grade One Pupils whose reading proficiency was categorized as Non-decoder, Beginning and Developing level based on Early Grade Reading Assessment (EGRA) results conducted last February, 2021. This action research is a quantitative study that employed single group experimental research design using EGRA as an Assessment Tool. The researchers analyzed the data obtained in the Pre-Test and Post-Test in terms of Decoding Skill and Sentence Reading Skill of the respondents. Then, t-test was used to compare the results of tests through employing Statistical Package for the Social Sciences (SPSS) software application. The result shows that there is a significant difference between the pre-test and post test scores of the Decoding Skill and Sentence Reading Skill as evidenced by the calculated t-value and p-value. Therefore, Project PFRATH is found to be effective in improving the reading performance of the Grade One pupils. Based on the findings, the researchers made the following recommendations. The school may adopt the Project PFRATH to intensify its Reading Program. Teachers from other grade levels may utilize the Project PFRATH as reading intervention to help pupils improve their reading skill. For future researchers, a similar study on Project PFRATH may be conducted in DepEd Schools.